Pengaruh Cash Effective Tax Rate, Pajak Tangguhan Dan Profitabilitas Terhadap Manajemen Laba (Study Kasus Perusahaan Index Idx30) - Pardosi, Habel; Hutabarat, Francis (Universitas 17 Agustus 1945 Jakarta, 2022)
Purpose of this study is determine to an influence Cash Effective Tax Rate, deferred tax and profitability for earnings management. Samples were taken from the IDX30 Index on the IDX 2018-2021. Then the samples were collected by purposive sampling method to obtain 27 samples. The analysis technique used is the classical assumption test, the significant F and t test, multiple linear regression analysis and the coefficient of determination test. The results show that there is a partial influence between Cash Effective Tax Rate, Deferred Tax, Profitability and earnings management of the IDX30 Index. Partially found, deferred tax and profitability have a significant effect on earnings management at a significance level of 10% (deferred tax) and 5% (profitability). The implications of the results of this study can be used by investors, if they want to detect the potential for earnings management, deferred taxes and profitability achieved by the company, can be used as a predictor of earnings management activity.